ANALYSIS OF LIQUIDITY RATIO FINANCIAL STATEMENTS IN PT. FINANSIA MULTI FINANCE (CREDIT PLUS) TO ASSESS COMPANY PERFORMANCE - Ayu Irma Setiyani (Universitas Islam Balitar, 2018)
This study aims to determine the financial performance of the company PT. Finansia Multi Finance (Credit Plus) in its financial statements for 3 periods from 20152017. The method used in this study is quantitative research. The data used in this study in the form of financial statements for 3 periods from 2015-2017 using a measure of ratio, namely liquidity. PT. Finansia Multi Finance (Credit Plus) in the current ratio shows the percentage, namely in 2015 3910% in 2016 537% and in 2017 567% means that in the current ratio the company is able to pay short-term debt using the company's current assets. Quick ratio shows the percentage of 2015 is 3876%, 2016 is 486% and 2017 is 507% which means that the company's ability to pay short-term debt without inventory increases. Cash ratio shows that in 2015 55%, 2016 92% and 2017 102% percentage obtained shows that the company is unable to pay short-term debt using cash